The natural history of COVID-19 in patients with inflammatory bowel disease: a nationwide study by the Hellenic Society for the study of IBD. Issue Volume 33:Issue S1(2021) (16th August 2021) - Bamias, Giorgos; Kokkotis, Georgios; Christidou, Angeliki; Christodoulou, Dimitrios K.; Delis, Vasileios; Diamantopoulou, Georgia; Fessatou, Smaragdi; Gatopoulou, Anthia; Giouleme, Olga; Kafritsa, Panagiota; Kalantzis, Chrisostomos; Kapsoritakis, Andreas; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: COVID-19 has evolved into a global health crisis, variably affecting the management of patients with chronic illnesses. Patients with inflammatory bowel disease (IBD) may represent a vulnerable population due to frequent administration of immune-modifying treatments. We aimed to depict the natural history of COVID-19 infection in Greek patients with IBD at a nationwide level via unbiased reporting of all cases that were registered during the sequential waves of the pandemic. Methods: Following a national call from the Hellenic Society for the study of IBD, we enrolled all IBD patients with established diagnoses of COVID-19. Clinical and epidemiological data, including COVID-19 modifying factors and IBD-associated therapies, were analyzed against adverse outcomes (hospitalization, ICU admission and death). Results: We identified 154 IBD patients who were diagnosed with COVID-19 (men: 58.4%; mean age=41.7 years [SD = 14.9]; CD: 64.3%). Adverse outcomes were reported in 34 patients (22.1%), including 3 ICU admissions (1.9%) and two deaths (1.3%). Multivariate logistic regression analysis showed that age (OR = 1.04, 95% CI, 1–1.08) and dyspnea at presentation (OR = 7.36, 95% CI, 1.84–29.46) were associated with worse outcomes of COVID-19 infection. In contrast, treatment with biologics, in particular anti-TNF agents, exerted a protective effect against an unfavorable COVID-19 disease course (OR = 0.4, 95% CI, 0.16–0.99). Patients on subcutaneous biologics were more likely to halt treatment due to the infection as compared to those on intravenous biologics. Conclusions: IBD patients who developed COVID-19 had a benign course with adverse outcomes being infrequent. Treatment with anti-TNF biologics had a protective effect, thus, supporting continuation of therapy during the pandemic.